Forming of size of counterbalancing overfall of pressure in hydraulic drive sensible to the change of loading, on the basis of multi-mode directional control valve - Petrov, O. V.; Kozlov, L. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Load-sensing hydraulic drive is developed on the basis of a multi-mode directional control valve that works with minimal power losses in different operation modes. Reduction of power losses is provided by maintaining constant value of the balancing pressure drop created with the help of pressure relief valve at the working port of the distribution spool of the multi-mode directional control valve.